Tożsamość narodu rosyjskiego w ujęciu Fiodora Dostojewskiego (Politeja, 2018)
Identity and the Russian Nation According to Fyodor DostoevskyThe nation occupies a central place in the works of Fyodor Dostoevsky, one that is closely connected with anthropological issues. For the author of The Devils, the nation constituted a collective entity based on the ethos of personalism, which is such a distinctive feature of Russian Orthodox thought. The immersion of the individual in the Orthodox community protects him against what Dostoevsky regarded as the pernicious and destructive individualism of European civilization. Thanks to this community, the Russian people can protect themselves against the degeneration of European nations and the rationalist consciousness that gave birth to the anti-Christian ideas of revolution and socialism. For Dostoyevsky, the identity of the Russian nation is infused with a sense of religious messianism combined with political messianism. This is a mystical-nationalistic messianism, which comes to the fore most emphatically in the conviction that Russia carries God within itself. It is the incarnation of God. It is this belief that fashions, in Dostoevsky’s opinion, the political mission of Russia – to provide brotherly protection for other Orthodox peoples and come to the rescue of a Europe in crisis. However, while in Dostoyevsky’s Christian anthropology the highest expression of the self is achieved through dialogue with another self, such interactions are not possible in the Russian nation’s relations other nations. The diversity of voices shaping the dialogue of nations does not correspond to the diversity of voices existing in interpersonal dialogues This is made impossible by the position and attitude of Russia as a nation serving a mission at two important levels of its existence: at the religious level and the political-state level. Not only in Dostoyevsky’s journalism, but also in the polyphony of his literary works, the Russian nation has a closed, non-polyphonic structure.